Heir to Sevenwaters - Marillier, Juliet (Marillier, Juliet. Sevenwaters novels, 2008)
After her newborn brother is kidnapped under her care, Clodoagh must enter the shadowy Otherworld and confront its powerful ruling prince in order to recover the heir to Sevenwaters.